Criminal Histories of Intimate Partner Homicide Offenders - Zeoli, April M. (Homicide studies, 2023)
This exploratory study investigates intimate partner homicide (IPH) offenders’ criminal histories to examine opportunities for criminal justice system intervention. Data were collected from the Michigan Violent Death Reporting System and Michigan State Police for the 117 IPHs committed in 2014 and 2015 in Michigan. Descriptive statistics on types of criminal charges and convictions for the 103 IPHs committed by aggressors (e.g., not in self-defense) are presented, with relatively few domestic violence charges or convictions. Twenty-nine percent of offenders had no criminal history. Findings highlight a need for more effective and greater implementation of interventions for both criminal justice system-involved and not-involved offenders.